The role of p53 in male infertility - Li, Jing; Huang, Xia; Luo, Lei; Sun, Jialin; Guo, Qie; Yang, Xue; Zhang, Chuanzhou; Ni, Beibei (Frontiers in Endocrinology, 2024)
The tumor suppressor p53 is a transcription factor involved in a variety of crucial cellular functions, including cell cycle arrest, DNA repair and apoptosis. Still, a growing number of studies indicate that p53 plays multiple roles in spermatogenesis, as well as in the occurrence and development of male infertility. The representative functions of p53 in spermatogenesis include the proliferation of spermatogonial stem cells (SSCs), spermatogonial differentiation, spontaneous apoptosis, and DNA damage repair. p53 is involved in various male infertility-related diseases. Innovative therapeutic strategies targeting p53 have emerged in recent years. This review focuses on the role of p53 in spermatogenesis and male infertility and analyses the possible underlying mechanism involved. All these conclusions may provide a new perspective on drug intervention targeting p53 for male infertility treatment.